2018
DOI: 10.1186/s13046-018-0853-9
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MIR31HG inhibits hepatocellular carcinoma proliferation and metastasis by sponging microRNA-575 to modulate ST7L expression

Abstract: BackgroundEmerging evidences have indicated that long noncoding RNAs (lncRNAs) play essential roles in the development and progression of cancers. Dysregulation of lncRNA MIR31HG has recently been reported in several types of cancers, and researches on the function of MIR31HG in cancers suggested that MIR31HG could act as either oncogene or tumor suppressor. But the functional involvement of MIR31HG has not been studied in hepatocellular carcinoma (HCC).MethodsIn this study, MTS assays, colony formation assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 38 publications
5
99
0
Order By: Relevance
“…Increasing numbers of research studies have reported that lncRNAs could serve as oncogenes or tumor suppressors through participating in regulation of proliferation, apoptosis, differentiation, and metastasis, implying they might be potential tumor biomarkers for diagnosis (Aguilo, Di Cecilia, & Walsh, ; Yan et al, ). For example, lncRNA MIR31HG suppresses HCC growth and invasion through inhibiting microRNA‐575 (miR‐575) to promote ST7L expression (Yan et al, ). LncRNA SNHG5 as an oncogene contributes to HCC progression through modulating miR‐26a‐5p/GSK3β signaling (Y. Li, Guo, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of research studies have reported that lncRNAs could serve as oncogenes or tumor suppressors through participating in regulation of proliferation, apoptosis, differentiation, and metastasis, implying they might be potential tumor biomarkers for diagnosis (Aguilo, Di Cecilia, & Walsh, ; Yan et al, ). For example, lncRNA MIR31HG suppresses HCC growth and invasion through inhibiting microRNA‐575 (miR‐575) to promote ST7L expression (Yan et al, ). LncRNA SNHG5 as an oncogene contributes to HCC progression through modulating miR‐26a‐5p/GSK3β signaling (Y. Li, Guo, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a general way, lncRNA functions as a competitive endogenous RNA by binding with microRNAs (miRNAs) to modulate messenger RNA (mRNA) expression in cancers (Qi et al, 2015). For instance, SNHG8 promotes the progression of endometrial via miR-152/c-MET axis (Yan et al, 2018). lncRNA SNHG14 drives the development of cervical cancer by sponging miR-206 and targeting YWHAZ (Ji, Wang, Bao, Yan, & Ji, 2019).…”
mentioning
confidence: 99%
“…Previous studies have revealed that cytoplasmic lncRNAs generally function as ceRNAs to regulate mRNA expression via sponging versatile miRNAs, thereby playing a pivotal role in cancer metastasis (Lian et al , ; Shan et al , ; Sun et al , ; Wang and Kong, ; Yan et al , ). In fact, lncRNAs exert their functions in several biological processes via interaction with DNA, proteins, and RNAs, which is dependent on the subcellular localization of the lncRNAs within the cells to a large extent (Chen et al , ).…”
Section: Discussionmentioning
confidence: 99%